EU public procurement policy: the economic crisis as trigger for enhanced harmonisation. Issue 4 (18th May 2020) - Pircher, Brigitte
ABSTRACT: While previous research on the impact of the economic crisis on EU policy has primarily focused on the internal market and financial market regulations, the effect on public procurement has so far been neglected. This lack of attention is surprising. Public procurement accounts for approximately 14% of the EU GDP and involves over 250.000 contracting public authorities. Therefore, procurement is considered essential for lifting the EU out of the crisis by promoting competitiveness and growth. Nevertheless, public procurement reflects contradictory developments. Whereas the European Commission strives for greater harmonisation, member states often focus on national priorities. By comparing the old and new procurement regimes through the lenses of historic institutionalism, this article demonstrates that the EU managed to enhance harmonisation despite tendencies of increased national protectionism. The article finds that procurement became a much more prominent policy instrument for greater market integration subsequent to the economic crisis.